Analysis of Presentation Delay in Patients with Advanced Breast Cancer Visiting Dharmais National Cancer Hospital - Iskandar, Iskandar; Padmawati, Retna Siwi; Hutajulu, Susanna Hilda; Fajrin, Meidina (Indonesian Journal of Cancer, 2024)
Background: Breast cancer is still one of the significant causes of the increasing mortality rate due to cancer. Treatment of breast cancer patients was delayed by 66.34%. The majority of patients arrive at stages IIIB and IV and are therefore treated at an advanced stage. This study aimed to analyze the factors causing the arrival delay of breast cancer patients to Dharmais Cancer Hospital with advanced stages. Methods: A descriptive study with a qualitative approach was used as the research design. Indepth interviews and document reviews were used to collect data. In-depth interviews were conducted with 12 advanced-stage breast cancer patients. Thematic data analysis was performed by tracing and identifying the main topics of the entire interview process. The triangulation method was used to validate the data by conducting interviews with 4 patient families and 2 oncology surgeons, as well as document review. Results: The presentation delay of advanced breast cancer patients was analyzed based on the interpretation and recognition of symptoms. There was an attitude of ignoring when there were symptoms and not seeking treatment. On psychological factors, there was a feeling of fear after being diagnosed and a sense of worry in the treatment process. On socioeconomic factors, there was no early detection, lack of information on early detection, waiting time constraints, and the selection of alternative treatments. Conclusions: Late-stage breast cancer patients were drawn to Dharmais Cancer Hospital due to issues with the interpretation and experience of symptoms, psychological issues patients reported, and socioeconomic difficulties during treatment. As a result, patients must be given additional care to deal with late arrivals, especially in cases of advanced breast cancer.